Dielectric properties of a monolayer nano-graphyne structure: Monte Carlo simulations. (November 2019) - Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Ousi Benomar, W.
Abstract: In this paper, the dielectric properties of a monolayer nano-graphyne structure, with mixed spins σ = 7/2 and S = 1, have been studied, using Monte Carlo simulations. Firstly, the ground state phase diagrams for a zero temperature value are reported and discussed. Secondly, the dielectric properties of the studied system for a non-zero temperature are examined. The effects of the temperature, the external longitudinal electric and crystal fields on polarization, dielectric susceptibility and hysteresis cycles have been investigated. Highlights: The thermodynamic and dielectric properties of a monolayer nano-graphyne structure using Monte Carlo simulations are investigated. The ground state phase diagrams are presented and discussed. Blocking temperature has been deduced for different physical parameters. The hysteresis cycles of a monolayer nano-graphyne structure are analyzed.